In Diversity is Strength - Equality, Human Rights and Diversity in the Arts - Moynihan, Mary (Irish Journal of Arts Management and Cultural Policy, 2020)
A review of the Arts Council/An Chomhairle Ealaíon Equality, Human Rights and Diversity Policy and Strategy and three year Action Plan for 2019 to 2021.